2020
DOI: 10.3390/molecules25030458
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Different Food-Grade Emulsifiers on the Properties and Stability of a Casein-Maltodextrin-Soybean Oil Compound Emulsion

Abstract: The improvement of food-grade emulsifiers in the properties and stability of complex emulsion has attracted much interest. In this study, the effects of six food-grade emulsifiers with a hydrophilic–lipophilic balance (HLB) range of 3.4–8.0 on a casein-maltodextrin-soybean oil compound emulsion were investigated by centrifugal precipitation rate (CPR), emulsifying activity index (EAI), microrheological properties, zeta potential, average particle size, and Turbiscan stability index (TSI). The optimal amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…There were no statistically significant differences between the computed determinants for the emulsions with EC-oleogels ( Figs 5-7), which means that the concentration of ethyl cellulose had no significant impact on the microrheological properties of the O/W emulsions. Liu et al (2020) indicated that the MS-DWS method allows for an analysis of the microrheological characteristics changes in emulsions in the context of the use of different types and concentrations of the food-grade additives, especially stabilizers. The emulsion with the addition of monogliceryde had the highest elastic strength and the greater macroscopic viscosity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no statistically significant differences between the computed determinants for the emulsions with EC-oleogels ( Figs 5-7), which means that the concentration of ethyl cellulose had no significant impact on the microrheological properties of the O/W emulsions. Liu et al (2020) indicated that the MS-DWS method allows for an analysis of the microrheological characteristics changes in emulsions in the context of the use of different types and concentrations of the food-grade additives, especially stabilizers. The emulsion with the addition of monogliceryde had the highest elastic strength and the greater macroscopic viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…The MVI parameter presents the macroscopic viscosity at zero shear. It is computed using the inverse of the slope value, and illustrates the viscosity changes (Pasqua et al, 2014;Liu et al, 2020). The emulsions were tested 24 h after they were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Defined as classical coarse dispersions, with multiple applications in pharmaceutical domain, emulsions are colloidal metastable systems composed of two immiscible phases, usually an oil and an aqueous phase (Leal-Calderon et al, 2007). The internal phase will be dispersed in a continuous phase and stabilized ideally with an emulsifier which is recognized for its contribution to the diminishing of the interfacial tension at the contact of the two phases being characterized by superficial and electrical properties (Liu et al, 2020). Simple ternary systems will be resulted, being known as O/W and W/O emulsions (Leal-Calderon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic data was unable to detect any structural changes between heat-treated and untreated samples. Multiple light scattering (Turbiscan analysis), which enables continuous monitoring of the optical properties of undiluted emulsion systems and provides real-time information on destabilization phenomena, was employed to determine the processing and storage effects on physical stability [ 41 ]. Particle size analysis showed that thermal processing had a significant incremental effect on oil droplet size at day 1 ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%